Independence Music Centre / Mohd Nazri Ab Rahim ... [et al.] - Ab Rahim, Mohd Nazri; Maarof, Abdul Hakeem; Abd Rashid, Azwan Zar; Nairn, Azrul; Kamaruzzaman, Mohd Hasrizal; Abdullah Lutfi, Ahmad Firdaus (Faculty of Electrical Engineering, 2002)
Music industries in our country exists since years and years ago. This industries is one of the thousand industries that can growth and the one that we can get profit in the blink of eyes. It gave so many opportunities to us. As an entrepreneur we must take this chances to make a business base on this industries. One of the ideal business is music centre. Because of that, we choose this business for our business plan.